The feeding of children from one to five years (London : His Majesty's Stationery Office)
1942-03 1942 1940s 24 pages 14 30. Sweet Twirls. Pastry. Filling. 1 1/2 lbs. Wheatmeal Flour. 6 Medium Carrots. 1 1/2 lbs. White Flour. 12 tablesp. Dried Milk. 3/4 lb. Cooking Fat. 6 tablesp. Dried Fruit or other preserves. 6 teasp. Baking Powder. Salt. Water to mix. Method : Prepare the pastry. Spread with the filling, roll up like a roly-poly, cut the roll into slices. Arrange the slices on a well greased baking tin and bake in a quick oven for 20 to 30 minutes. 31. Foundation Pudding. Foundation Recipe. 3 lbs. Flour or 2 lbs. Flour and 1 lb. raw Potato (grated) or fine Oatmeal. 3 Carrots (grated) (1 lb.). 4 teasp. Bicarbonate of Soda. Pinch of Salt. 3/4 lb. Suet or Margarine. Milk to mix. 3/4 lb. Sugar. Variations to Foundation Mixture. 1. 1/4 lb. Cocoa and extra Sugar. 2. 3/4 lb. Dried Fruit — Raisins, Sultanas, chopped Dates. 3. 3/4 - 1 lb. Jam, Syrup, Marmalade. Method : Mix dry ingredients thoroughly. Add finely chopped suet or rub in margarine. Add grated carrots and cocoa or dried fruit — if used. Mix to a fairly stiff mixture with milk or milk and water. Turn into greased basins and steam 2-3 hours for 1/2 lb. mixture. NOTE. 1. When using Jam, Syrup or Marmalade, divide into equal portions and place in the bottom of each basin before adding the mixture. 2. Alternative Method : Bake in greased Yorkshire tins 3/4 - 1 hour. 32. Milk Pudding. 16 pints Milk. 1 lb. Sugar. 1 1/2 lbs. Cereal. Method : Wash cereal and add sugar and milk. Bake in moderate oven in pie dishes or hot-pots 2—3 hours or cook in double pan. 33. Chocolate Queen of Puddings. 5 lbs. Bread — stale pieces. 12 Eggs or Dried Eggs, 10 pints Milk. 1 1/4 lbs. Sugar. 4 oz. Cocoa. Method : Blend cocoa in a little cold milk. Add to half the milk and heat it with the sugar. Pour over sliced bread — soak for one hour. Beat eggs (soak if dried) and add remainder of milk. Pour on to soaked bread. Put into greased dishes and bake in moderate oven until set — 1 hour. 34. Cocoa Cap Custard. 16 pints Milk. 1 1/2 lbs. Sugar. 1 lb. Custard Powder. 1/4 lb. Cocoa. Method : Make custard as for blancmange, using half the sugar. Sprinkle custard with remaining sugar and cocoa mixed. 127/NU/5/5/1/28